Effects of time pressure, type of shopping, and store attributes on consumers' satisfaction with grocery shopping. Issue 4 (8th August 2017) - Nilsson, Elin; Gärling, Tommy; Marell, Agneta
Abstract: The aim of this study is to investigate whether satisfaction with grocery stores is affected by type of grocery shopping in conjunction with time pressure, and which attributes are important for satisfaction. Fictitious grocery stores are constructed according to a fractional factorial design by varying access, price level, supply quality/range, and service quality . In an Internet survey, 1023 Swedish consumers rated satisfaction with major vs. fill-in shopping imagining they were under high or low time pressure. The results showed that satisfaction is higher for fill-in shopping than major shopping, that time pressure has no effect on satisfaction, and that price level, service quality, and product quality/range are more important for satisfaction with major shopping, whereas access is more important for satisfaction with fill-in shopping. It is also found that the importance of attributes for satisfaction depends on type of shopping more than on individual characteristics.